RHYTHM OF INFLUENCE: A COMPARATIVE ANALYSIS OF THE BEATLES AND BTS IN POPULAR CULTURE. - Rengan, Rahul; Chellirian, B. Sonia (International Journal of Research -GRANTHAALAYAH, 2024)
A comparative study of Rock n Roll and K-POP through popular culture focusing on “The Beatles” and “The BTS.” The study examines the identity of two generations from the perspective of popular culture. It also investigates the historical, cultural, and economic background of two generations and the changing process of the production and consumption of popular music of that Era. The study analyzes their musical styles, lyrical themes, fan engagement strategies, and the ways in which they have influenced popular culture globally. Popular culture is the set of practices, beliefs, and objects that embody the most broadly shared meanings of a social system. Music, one of the most important elements of the culture, has emerged with a unique style. In today’s improving and ever-changing conditions, music has become an element which almost everybody in society encounters, benefits from and